The Environmental Legal Responsibility of Cigarette Companies in Community Economic Empowerment - Suparnyo Suparnyo; Dwiyana Achmad Hartanto; Yusuf Istanto; Wahyu Edy Amrulloh; Rizal Bagus Prabowo (Unissula, 2024)
Legal and environmental responsibility is part of a concept in business known as corporate social responsibility, because the concept of corporate social responsibility broadly includes responsibility in the economic and environmental sectors. This study aims to examine the strategy for implementing legal responsibility in the social and environmental sectors in empowering the community's economy and the forms of implementing corporate social responsibility in the social/community sector. Through an empirical or non-doctrinal legal approach with primary and secondary data and using qualitative analysis, answers to this research question can be found. The results of the study state that the strategy for implementing social responsibility in the social/community sector is carried out through several strategies, namely identifying stakeholders, setting priorities, focusing on important issues, partnerships with external parties and companies, transparency and reporting, as well as measurement and evaluation to achieve a balance between achieving profits and social and environmental responsibilities. Several large cigarette companies in Kudus have carried out their Corporate Social Responsibility obligations through several activities such as empowering Village-Owned Enterprises, empowering MSMEs and holding training related to empowering the community's economy.